A Survey of The Design and Security Mechanisms of The Wireless Networks and Mobile Ad-Hoc Networks. Issue 1 (December 2020) - Kumar, Keshav; Verma, Sahil; Kavita; Jhanjhi, NZ; Talib, M N
Abstract: In this paper, we are going to evaluate various wireless network security related issues and how do they affect the quality of service of a wireless network and Mobile AdHoc Networks(MANETs). The time systems are increasingly required Getting educated more and more. Systems are simple Drastically converting the structure into more functional and dynamic. Computer networks have undergone a major move from cable to wireless A recent development has been networks and fast wireless infrastructure. MANET has appeared between many other cellular networks. Why? Why? dynamic topology without any centralization, conventional path MANETs do not comply with protocols and authentication systems. These MANETs are responsive to a lot of people It is not feasible in other networks to attack and participate in disruptive operations. A Wireless Network can be a very vulnerable entity and is always susceptible to various types of attacks and attackers, we are going to discuss a few of these attack and how do they affect the overall network performance, finally we are going to evaluate some of the solutions offered and how they improve the network.